'I'm in love with someone that doesn't exist!' Bleed in the context of a computer game. Issue 3 (13th September 2011) - Waern, Annika
It is not unusual for computer games to include romance, but it is unusual for a computer game to create strong romantic reactions in players. In this article I investigate the romantic experience in the game Dragon Age: Origins. Based on an investigation of blog and community comments, I argue that the game creates a 'bleed' effect: some players, to some extent, fall in love with the characters that they are romancing in the game. The article identifies some specific aspects of the game design that contribute to the effect; apart from storyline and character design I discuss the desire for safe-zone romance and the phenomena of player projection as contributing to the effect.